Imaginary and Real Bridges as Connecting Elements in Communal Relations? - Retterath, Hans-Werner (Ethnographica et Folkloristica Carpathica, 2024)
The meaning of bridges is often mentioned in town twinning and other international contacts. In general, this word has positive connotations, as bridges enable interaction and communication and ideally create close relationships. Bridges are usually referred to in a metaphorical sense, but in sometimes they are real structures, such as those dedicated to a specific partner or between two partner communities from different countries. While the significance of the former is symbolic, the latter also fulfill a function in the real sense. In a figurative sense, common elements of everyday life can also form a bridge and bring people together, such as customs, origins, sources of economic income, geographical location and historical experiences. Real bridges can not only connect people and cities, but also act as monuments that remind us of a relationship again and again. By describing selected examples of imaginary and real bridges, the article also addresses the following questions: Is the bridge metaphor mostly just an empty phrase? How are imaginary and real bridges perceived by the public? Are imaginary bridges (e.g. relevant activities, everyday cultural similarities) and physical bridges really connecting elements in European diversity? To what extent are they helpful in understanding the foreign? The article draws primarily on the author's many years of research into town twinning but also on a number of other bilateral relationships in the Central European context. Observations, surveys, media analyses and other research tools serve as sources.